An honest lie ebook A domestic thriller. - Fisher, Tarryn (2022)
From the #1 New York Times Bestselling Author of Never Never, co-written with Colleen Hoover! "An Honest Lie is riveting suspense, but it's also a scream of defiance, a howl of rage."—Colleen Hoover, #1 New York Times bestselling author They've taken your friend, but only to get to you. What do you do? Lorraine—"Rainy"—lives at the top of Tiger Mountain. Remote, moody, cloistered in pine trees and fog, it's a sanctuary, a new life. She can hide from the disturbing past she wants to forget. If she's allowed to. When Rainy reluctantly agrees to a girls' weekend in Vegas, she's prepared for an exhausting parade of shots and slot machines. But after a wild night, her friend Braithe doesn't come back to the hotel room. And then Rainy gets the text message, sent from Braithe's phone: someone has her. But Rainy is who they really want, and Rainy knows why. What follows is a twisted, shocking journey on the knife-edge of life and death. If she wants to save Braithe—and herself—the only way is to step back into the past. How far will one twin go to uncover where her "good half" has gone? Find out in Good Half Gone, #1 New York Times Bestselling author Tarryn Fisher's next twisty psychological thriller! Looking for more captivating reads by Tarryn Fisher? Don't miss: Never Never The Wives The Wrong Family